What do your lockdown reading habits reveal? - Hasan, Md. Mahmudul (2020)
The days of COVID-19 have given many of us mental space to introspect and to think clearly and differently. Perhaps it is important to remind people of all persuasions of the benefits of reading that can remedy boredom and overcome anxiety. Reading can be a good way to spend spare time. It is a panacea for the ennui of the educated, especially during the lockdown period. In most cases, readers do not have to follow any schedule and can consult reading materials in their own time and space.